Risk-oriented approach to ecological safety management at oil refinery - G. A. Fomenko (Real Economics Publishing House, 2018)
The article considers place and role of the risk-oriented approach in environmental management at enterprises, describes mechanisms for use of risk assessment in environmental management processes and documents, tools for use of risk characteristics in development and implementation of programmes and plans for oil refineries.The study relevance is based on the need to improve the environmental management system of “Orsknefteorgsintez” in line with the plans to include risk-oriented approach in supervisory work, including state environmental supervision.The main goal of the work was development of approaches to risk-oriented environmental management at “Orsknefteorgsintez” based on the health risk assessment from environment pollution, followed by interpretation of gained data and appropriate management decisions.The research was conducted in two stages. The first stage included health risk levels determination resulted from air pollution by “Orsknefteorgsintez”. The results included hygienic studies of human health risk assessment from negative impact by “Orsknefteorgsintez” considering the implementation of the middle-term enterprise development program; and results of comparative analysis of human health risk levels prior to and after operational commissioning of reconstructed objects within the middle-term enterprise development program. The recommendation on human health risk management from the “Orsknefteorgsintez” production facilities (including control and monitoring) are based on the results of the first stage.Risk-oriented improves environmental management systems at enterprises, helps in interactions with government bodies, enhances management decisions in line with environmental legislation and increases environmental-economic investment efficiency.